2022
DOI: 10.3390/ijerph19052722
|View full text |Cite
|
Sign up to set email alerts
|

Does the Back Plate Position Influence Swimming Start Temporal Characteristics?

Abstract: The current study examined the back plate position impact on the block phase movement pattern and total starting performance with a distinction for sex. Thirty-eight swimmers performed starts changing the back plate position (preferred position, one position forward and one position backward), with the data being assessed using a 3D dynamometric central and a video camera. In males, the 15 m start time was 0.1 s shorter for the preferred position compared with the backward position (p < 0.05). Regardless of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The advantages provided by OSB starting blocks or their platforms lie in the rear support and its adjustment, which allows displacement in five positions. This change in the start block has led to some research [ 2 , 4 , 6 , 7 , 12 , 13 , 20 ], which have addressed the adjustment of the backrest or the change of the base position on the start block, which affect the kinematic–dynamic parameters in the on-start block phase, the kinematic parameters in the flight and underwater phases, as well as the take-off performance itself. For example, a study by Cicenia et al [ 21 ] looked at the use of shin length as a measure to determine cleat position and its effect on performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages provided by OSB starting blocks or their platforms lie in the rear support and its adjustment, which allows displacement in five positions. This change in the start block has led to some research [ 2 , 4 , 6 , 7 , 12 , 13 , 20 ], which have addressed the adjustment of the backrest or the change of the base position on the start block, which affect the kinematic–dynamic parameters in the on-start block phase, the kinematic parameters in the flight and underwater phases, as well as the take-off performance itself. For example, a study by Cicenia et al [ 21 ] looked at the use of shin length as a measure to determine cleat position and its effect on performance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we can distinguish three basic positions in the base position on the start block-front-, neutral-, and rear-weighted [ 1 , 15 , 25 , 26 ], with neutral-weighted and weighted being confirmed in some studies [ 1 , 5 , 9 ]. A change in baseline position can directly affect performance on the start block (block time), either positively or negatively [ 2 , 4 , 24 , 27 ], or there may be no difference at all [ 6 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variables selected for further analysis are described in Table 1 . These variables are also included on a regular basis in studies evaluating swimming starts ( Tor et al, 2014 ; de Jesus et al, 2022 ; Rudnik et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Investigations on swimming start have been developed based on different concerns, mainly to understand the kinematic and kinetic variables of the foregoing start styles [6,9,10,11]. For instance, studies have shown that (i) grab start involves greater flight displacement [12] and smaller reaction [13,14] than track start; (ii) reduced block time depends on the increase in the vertical and horizontal velocities in the grab and track starts, respectively [15]; (iii) effective starts are related to the higher peaks of force [16,17]; and (iv) training improves the peak horizontal force, velocity of takeoff, and block and flight times [18,19]. Currently, the track start has been seen as a more efficient than grab start [20].…”
mentioning
confidence: 99%